PERBEDAAN PRESTASI BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GI DAN TIPE STAD DITINJAU DARI TINGKAT MOTIF BERPRESTASI SISWA - Harjanto, Ambyah (Lentera: Jurnal Ilmiah Kependidikan, 2015)
The aim of this study is to describe: (1) the interaction between cooperative learning and achievement motivation towards mathematics achievement, (2) the differences between students’ mathematics achievement who learned through Cooperative Learning Type GI and STAD, (3) the differences between students’ mathematics achievement who learned through cooperative Learning Model Type GI and STAD on students with high achievement motivation, (4) the differences between students’ mathematics achievement who learned through cooperative Learning Model Type GI and STAD on students with low achievement motivation.The conclusion of this study are: (1) there is an interaction between cooperative learning and achievement motivation towards students’ mathematics achievement; (2) the cooperative learning model of GI type give lower mathematics achievement than cooperative learning model of STAD type; (3) on students with higher achievement motivation, the cooperative learning model of GI type gives mathematics achievement is higher than STAD type; (4) on students with lower achievement motivation, the cooperative learning model of GI type gives mathematics achievement is lower than STAD type.